Relation between waist circumference and the renal hemodynamic in healthy individuals - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Nutrition Metabolism and Cardiovascular Diseases, 2024)
Background and aims: Obesity has been shown to be an independent risk factor for the development of CKD. Little is known about pathways of interaction of visceral fat mass estimated by waist circumference (WC) and metabolic factors with the renal and intraglomerular hemodynamic profile in healthy, non-obese individuals. Methods and results: The study population of this post-hoc analysis in 80 healthy individuals, who participated in a randomized, controlled clinical trial (www.clinicaltrials.gov: NCT02783456) was divided into two groups based on median of WC (high WC and low WC group). Renal hemodynamic profiles were analyzed using steady state input clearance (infusion of para-amino-hippuric acid and inulin). Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated (Gomez equation). The analysis included healthy, non-smoking individuals, aged 27 ± 9 years with median WC of 84.75 ± 9 cm. Glomerular filtration rate (GFR) (110 ± 15 vs. 127 ± 16 ml/min/m2, p < 0.001), renal plasma flow (RPF) (620 ± 109 vs. 700 ± 104 ml/min, p = 0.001) and IGP (36.7 ± 2.3 vs. 38.5 ± 3.1 mmHg, p = 0.003) were lower in the high WC compared to the low WC group. Patients in the high WC group showed higher renal vascular resistance (RVR) (85 ± 19 vs. 70 ± 12 mmHg/(ml/min), p < 0.001), higher RA (4034 ± 1177 vs. 3069 ± 786 dyn∗s/cm5, p < 0.001) and higher RE (2283 ± 339 vs. 2118 ± 280 dyn∗s/cm5, p = 0.021) compared to the low WC group. Individuals in the high WC group showed higher leptin levels (p = 0.003) and higher HOMA-IR (p = 0.024) compared to the low WC group. Conclusion: Increased WC in healthy young individuals was associated with reduced GFR and RPF likely mediated by increased RVR.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Clearance analysis; Obesity; Renal hemodynamic; Waist circumference